Pengaruh Pendapatan Dan Pendidikan Terhadap Konsumsi Rumah Tangga Miskin Di Nagari Panti Timur Kecamatan Panti Kabupaten Pasaman - Deni Pratama Saputra; Yuwarman Mansur (Sharing: Journal of Islamic Economics Management and Business, 2025)
The background for choosing this title is poverty which is a problem in an area. No exception in Nagari Panti Timur, Panti District, Pasaman Regency. This study aims to determine the effect of income and education on household consumption in Nagari Panti Timur. This research is a quantitative study with multiple regression analysis. This data was obtained by distributing research questionnaires to 86 respondents in Nagari Panti Timur. The results of this study show that the multiple regression equation is Y = 2.422 + 0.655X1 + 0.251X2. (1) In general, respondents responded to the data test with the question that the income and education variables were related to household consumption in Nagari Panti Timur. (2) From the results of the t test it is known that the partial test value of the income variable shows a significance of 0.000 <0.05 and the calculated t value is 5.557 > 1.988 so that it can be seen that H1 is accepted. The partial test value of the education variable shows a significance of 0.028 <0.05 and a t-count value of 2.236 > 1.988 so that it can be seen that H2 is accepted. Thus it can be concluded that the variables Income and Poverty affect Household Consumption in Nagari Panti Timur. (3) From the results of the simultaneous test it can be seen that the value of the simultaneous test is at a significance of 0.000 which means it has a value <0.05 and an F count value of 75.163 > F table 3.10. Then H3 is accepted. So it can be concluded that income and education simultaneously influence the consumption of poor households in Nagari Panti Timur. (4) From the output results on the coefficient of determination in the R square column, the value is 0.644. The value of the coefficient of determination is changed in percentage to 64.4%. So it can be concluded that 64.4% of poor household consumption is influenced by income and education.